2022
DOI: 10.1177/1934578x221130699
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and Ex vivo Antioxidant Activity and Sustained Release Properties of Sinomenine-Loaded Liposomes-in-Hydrogel Biomaterials Simulating Cells-in-Extracellular Matrix

Abstract: Sinomenine (SIN), a natural product, has been used to treat rheumatoid arthritis (RA) in China for thousands of years. SIN has been developed for the treatment of RA by way of tablets and injections, but both dosage forms have been associated with severe adverse reactions. Making SIN into liposomes-in-hydrogel biomaterials for external use has a good slow-release effect and can play an important role in avoiding the first-pass effect, gastrointestinal reaction, and increasing the local action time of drugs. SI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Their findings indicated that SIN had a significant clearance of DPPH (IC 50 = 25.5 μM) and H 2 O 2 (IC 50 = 1.1 mM) and reduced MDA in organs. The DPPH scavenging rates of SIN and its three preparations were ranked as SIN > SIN-L > SIN-H > SIN-L-H. SIN-L, SIN-H, and SIN-L-H (0.6 mM) exhibited similar H 2 O 2 clearance rates, with the drug release being slow and lower than that of SIN alone [ 215 ]. The comprehensive details of the antioxidant activity of SIN are summarized in Table 13 .…”
Section: Antioxidant Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Their findings indicated that SIN had a significant clearance of DPPH (IC 50 = 25.5 μM) and H 2 O 2 (IC 50 = 1.1 mM) and reduced MDA in organs. The DPPH scavenging rates of SIN and its three preparations were ranked as SIN > SIN-L > SIN-H > SIN-L-H. SIN-L, SIN-H, and SIN-L-H (0.6 mM) exhibited similar H 2 O 2 clearance rates, with the drug release being slow and lower than that of SIN alone [ 215 ]. The comprehensive details of the antioxidant activity of SIN are summarized in Table 13 .…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…The clinical application of sinomenine is constrained by its short half-life, high required concentration and low drug utilization [ 10 , 14 , 232 ]. Efforts to enhance sinomenine’s absorption rate and sustained release performance, such as incorporating it into hydrogels, are still in the nascent stages and require further validation [ 215 ]. Currently, sinomenine is administered primarily through injections, capsules, tablets, and patches [ 233 ], with limited research being conducted on improving drug absorption based on sinomenine derivatives.…”
Section: Conclusion or Concluding Remarksmentioning
confidence: 99%
“…SH can protect the brain from ischemic injury by inhibiting MMP-9 overexpression by controlling inflammatory responses and enhancing the permeability of the blood-brain barrier (BBB) [23]. SH is also thought to inhibit the expression of MMP-2 and MMP-9, which may inhibit glioma cell migration and invasion by inhibiting P13K/Akt signaling.…”
Section: Introductionmentioning
confidence: 99%